Laparoscopic Cholecystectomy and Common Bile Duct Exploration in Situs Inversus Patients - Simkhada, S.; Malla, B.; Shrestha, R. (Kathmandu University Medical Journal, 2021)
Situs inversus is a congenital condition in which the major visceral organs are reversed from their normal positions, estimated to occur in 1 in 5000–20,000 births. Incidence of gallbladder stone disease is same in these patients and normal patients. Laparoscopic cholecystectomy remains the treatment modality, and performing it successfully in these patients even rarer. We report a 54 years gentleman with gall stone, and 63 years lady who had both gall stone and common bile duct stone along with situs inversus. The mirror image reversibility of the abdominal viscera was seen in both cases. Ports were placed on the opposite side as the liver and the gallbladder were on the left side. Dissection was difficult because being a right-handed surgeon, the non-dominant hand would be the working hand. However, no perioperative complications occurred. It is technically challenging and requires a proper orientation of the left upper quadrant of abdomen.